A 2/1 Sunitinib Dosing Schedule Provides Superior Antitumor Effectiveness and Less Toxicity Than a 4/2 Schedule for Metastatic Renal Cell Carcinoma: A Systematic Review and Meta-Analysis - Deng, Huan; Li, Meng; Wu, Qian; Wang, Li; Hong, Zhengdong; Yi, Fengming; Wei, Yiping; Zhang, Wenxiong (Frontiers in Oncology, 2020)
Background: The standard sunitinib schedule to treat metastatic renal cell carcinoma (mRCC) is 4 weeks on/2 weeks off (4/2). However, some studies revealed intolerable adverse events (AEs) in patients on this schedule. An alternative schedule, 2 weeks on/1 week off (2/1), may overcome this issue. This meta-analysis was performed to compare the effectiveness and toxicity between the 2/1 and 4/2 sunitinib dosing schedules. Methods: We acquired relevant studies by searching PubMed, ScienceDirect, the Cochrane Library, Scopus, Ovid MEDLINE, Embase, Web of Science, and Google Scholar. Our main endpoints included overall survival (OS), progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and AEs. Results: We identified 9 medium- and high-quality studies. Both schedules were effective for mRCC, with comparable OS and similar ORR. However, the 2/1 schedule had better PFS (hazard ratio (HR) = 0.81, 95% confidence interval [CI]: 0.66-0.99, P= 0.04), higher DCR (risk rate (RR) = 1.22, 95% CI: 1.01-1.47, P= 0.04) and fewer dosage interruptions (RR= 0.60, 95% CI: 0.43-0.84, P= 0.003). Additionally, the 2/1 schedule elicited fewer specific severe AEs, including thrombocytopenia/platelet disorder, hand-foot syndrome, hypertension and fatigue. In our subanalysis, PFS was better among East Asians using the 2/1 schedule than among other populations (HR= 0.75, 95% CI: 0.58-0.98, P= 0.03), and patients administered an initial dosage of 50 mg/d on the 2/1 schedule had superior PFS (HR= 0.76, 95% CI: 0.59-0.97, P= 0.03) than those others. Conclusions: These findings suggest that the 2/1 schedule is more suitable for mRCC than 4/2, due to superior PFS, better DCR and fewer AEs. Nevertheless, more large-scale studies with good quality are needed.